2004
DOI: 10.1103/physrevlett.92.123906
|View full text |Cite
|
Sign up to set email alerts
|

Lasing Action due to the Two-Dimensional Quasiperiodicity of Photonic Quasicrystals with a Penrose Lattice

Abstract: We have fabricated photonic quasicrystal lasers with a Penrose lattice that does not possess translational symmetry but has long-range order, and observed coherent lasing action due to the optical feedback from quasiperiodicity, exhibiting a variety of 10-fold-symmetric lasing spot patterns. The lattice constant dependence of lasing frequencies and spot patterns show complicated features very different from photonic crystal/random lasers, and we have quantitatively explained them by considering their reciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 12 publications
3
118
0
Order By: Relevance
“…[11][12][13][14][15] Recently, a wide interest has been attracted to the bandedge states in quasiperiodic composites. 4,[16][17][18][19][20][21][22][23] Firstly, the property of wave functions at band edges in quasiperiodic structures remains an interesting and unresolved topic. 24 By observing the liquid surface wave on a quasiperiodically drilled bottom, the wave function at the band edge is shown to be a plane wave with quasiperiodic modulation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[11][12][13][14][15] Recently, a wide interest has been attracted to the bandedge states in quasiperiodic composites. 4,[16][17][18][19][20][21][22][23] Firstly, the property of wave functions at band edges in quasiperiodic structures remains an interesting and unresolved topic. 24 By observing the liquid surface wave on a quasiperiodically drilled bottom, the wave function at the band edge is shown to be a plane wave with quasiperiodic modulation.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] However, recent studies showed that the band-edge states in photonic quasicrystals can support various applications with novel and promising properties that are unrealizable by using the band-edge states in photonic crystals. [17][18][19][20][21] For example, lasing action of tenfold rotational symmetry at the band-edge states has been observed in photonic quasicrystals with a Penrose lattice. 17 Higher-order harmonic generations with more flexibility, [18][19][20] even simultaneous phase matching of arbitrary optical frequencyconversion processes, 21 have been investigated in nonlinear photonic quasicrystals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations